2020
DOI: 10.1021/acsomega.0c02045
|View full text |Cite
|
Sign up to set email alerts
|

Successful Reduction of Neointimal Hyperplasia on Stainless Steel Coronary Stents by Titania Nanotexturing

Abstract: Bare metal stents (BMSs) of stainless steel (SS) were surface engineered to develop nanoscale titania topography using a combination of physical vapor deposition and thermochemical processing. The nanoleafy architecture formed on the stent surface remained stable and adherent upon repeated crimping and expansion, as well as under flow. This titania nanoengineered stent showed a preferential proliferation of endothelial cells over smooth muscle cells in vitro, which is an essential requirement for improving the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The nanoleafy structures were found to be extremely stable and adherent upon stent crimping and expansion with good corrosion resistance. 103 This titania nanotexturing developed on SS bare-metal coronary stents presented minimal in-stent restenosis, effective endothelialization, and no thrombus formation after 8 weeks of implantation in a rabbit iliac artery model, 104 as evident from Figs. 3(d)–3(f) .…”
Section: Introductionmentioning
confidence: 78%
“…The nanoleafy structures were found to be extremely stable and adherent upon stent crimping and expansion with good corrosion resistance. 103 This titania nanotexturing developed on SS bare-metal coronary stents presented minimal in-stent restenosis, effective endothelialization, and no thrombus formation after 8 weeks of implantation in a rabbit iliac artery model, 104 as evident from Figs. 3(d)–3(f) .…”
Section: Introductionmentioning
confidence: 78%
“…Another method to fabricate nanowires structures on stents ( Fig. 7 b) was proposed by Mohan et al [ 72 ], who claimed the selective promotion of the proliferation of HUVECs and less in-stents restenosis. The nanowire surface structures were fabricated by thermal hydrolysis of Ti coatings which is sputter coated (also known as CVD) on stainless steel.…”
Section: Effects Of Topography and Surface Chemistry On Stentsmentioning
confidence: 99%
“…Behaviours are then strongly affected by ligand density and features orientation. Round, relative flatten, fine and large amount of ligand usually provide a high potential for improvement of endothelial cells which is around 50–70 μm long, 10–30 μm wide and 0.1–10 μm thick [ 78 ], such as randomly roughened surfaces with roughness ranging in the nano to submicron scale [ 43 , 44 , 46 , 48 ], nano pillar surfaces [ 61 , 62 ] and nanowire surfaces [ 71 , 72 ]. If the features have preferential orientation or the arrangement of features is anisotropic, features then provide an oriented guidance for cell growth and migration, as demonstrated by the strong alignment of smooth muscle cells on groove structures [ 49 ].…”
Section: Effects Of Topography and Surface Chemistry On Stentsmentioning
confidence: 99%
“…It was recently shown that the specific nanotopography of TiO 2 used for cardiovascular stents can improve their bio-/hemo-compatibility via the increased adhesion and growth of human coronary artery endothelial cells and reduced adhesion and activation of platelets [ 3 ]. The surface nanostructurization of titanium (specifically the formation of TiO 2 nanotubes with different diameter) was shown to alter physicochemical properties, such as wettability [ 2 ] and surface chemistry, which consequently affect the interactions of TiO 2 nanostructured surfaces with cells [ 3 , 47 , 58 ]. In vivo studies have shown improved endothelization and reduced neointimal thickening on nanostructured stents compared to bare-metal stents [ 58 ].…”
Section: Interaction Of Cells With Nanostructured Surfacesmentioning
confidence: 99%
“…The surface nanostructurization of titanium (specifically the formation of TiO 2 nanotubes with different diameter) was shown to alter physicochemical properties, such as wettability [ 2 ] and surface chemistry, which consequently affect the interactions of TiO 2 nanostructured surfaces with cells [ 3 , 47 , 58 ]. In vivo studies have shown improved endothelization and reduced neointimal thickening on nanostructured stents compared to bare-metal stents [ 58 ]. Moreover, the study performed by Peng et al [ 59 ] showed that the TiO 2 nanotubular surface significantly enhances endothelial cell proliferation, while, at the same time, the growth of vascular smooth muscle cells is reduced.…”
Section: Interaction Of Cells With Nanostructured Surfacesmentioning
confidence: 99%